PEOPLE'S BUSINESS CREDIT MEDIATES THE QUALITY OF FINANCIAL REPORTS, FINANCIAL INCLUSION, AND DIGITAL BANKING ON THE PERFORMANCE AND RESILIENCE - Harmadji, Dwi Ekasari; Yuliana, Rachma (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The background of this paper highlights that Micro, Small, and Medium Enterprises (MSMEs) play a key role in the Indonesian economy. They contribute 61.9% to the Gross Domestic Product and support over 64.2 million business units. However, MSMEs still struggle with access to financing, the quality of financial reports, and the use of digital technology. This study aims to explore how People's Business Credit (KUR) mediates the relationship between the quality of financial reports, financial inclusion, digital banking, and the performance and resilience of MSMEs in Malang City.  The research uses a descriptive quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) version 4 method. The sample consisted of 384 MSMEs in Malang City, selected through purposive sampling. Data were gathered using a structured questionnaire with a Likert scale of 1-5. The SEM-PLS analysis reveals the following results: (1) the quality of financial reports positively and significantly affects KUR access (β=0.742, p<0.001), (2) financial inclusion positively affects KUR access (β=0.681, p<0.001), (3) digital banking positively affects KUR access (β=0.723, p<0.001), (4) KUR positively affects MSME performance (β=0.765, p<0.001), and (5) KUR positively affects MSME resilience (β=0.698, p<0.001).  The model shows an R-square value of 0.689 for MSME performance and 0.612 for MSME resilience. The findings confirm that KUR effectively mediates the improvement of MSME performance and resilience through the quality of financial reports, financial inclusion, and digital banking. These results have significant implications for the development of sustainable MSME financing policies.